Strategic application of liposomal system to R-α-lipoic acid for the improvement of nutraceutical properties. (3rd June 2022) - Halder, Shimul; Mibe, Yasuhiko; Rikimura, Shingo; Kuromi, Koichi; Sato, Hideyuki; Onoue, Satomi
Abstract: R-α-lipoic acid (RLA) and dihydrolipoic acid (DHLA), a reduced form of RLA, are potent endogenous antioxidants that can reduce oxidative damage. Despite their numerous nutraceutical potentials, clinical applications of RLA are still limited due to its poor solubility and stability problems. This study aimed to develop an RLA-loaded liposome (LIP/RLA) for the improvement of nutraceutical properties. LIP/RLA was developed by a typical solvent injection method. Uniform liposomes of LIP/RLA were observed by transmission electron microscopy, and the mean particle size was calculated to be ∼150 nm from the data of dynamic light scattering. LIP/RLA could prevent the degradation of RLA even under acidic conditions (pH 1.2) possibly due to the encapsulation of RLA into the liposomal structure. In the release test under pH6.8 with lipase, LIP/RLA showed relatively rapid release of RLA, possibly due to the lipolysis of phospholipids by lipase. After the oral administration of LIP/RLA (10 mg-RLA/kg, p.o. ) in rats, the systemic exposures of RLA and DHLA increased by 2.8- and 5.8-fold, respectively. In a rat model of acute hepatic injury induced by carbon tetrachloride (CCl4 ) (0.7 mL-CCl4 /kg, p.o. ), orally dosed LIP/RLA (3 mg-RLA/kg, p.o. ) resulted in 78.7% and 86.4% reductions of plasma alanine aminotransferase, and aspartate aminotransferase, respectively; however, RLA was found to be less effective possibly due to the poor oral absorption. The RLA-loaded liposomal system might be a promising carrier for poorly water-soluble materials with poor stability under acidic conditions, as well as RLA, to improve their oral absorption and nutraceutical properties.